2012
DOI: 10.1002/dmrr.1285
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine treatment reverses depressive‐like behavior in alloxan‐diabetic rats

Abstract: In conclusion, this study demonstartes a link between diabetes and depression in rats and that imipramine exerted antidepressant effects in diabetic animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…It is important to note that during the formation of memories the activation of specific receptors and of several molecular cascades is required to convert extracellular signals that lead to changes in neuronal connectivity [34], which were probably not altered in the brains of alloxan-induced diabetic rats. For example, we recently demonstrated that brain-derived neurotrophic factor (BDNF) levels did not alter in the hippocampus from alloxan-induced diabetic rats [35]. BDNF is a neurotrophin which has an important role in hippocampal-dependent forms of memory [36].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that during the formation of memories the activation of specific receptors and of several molecular cascades is required to convert extracellular signals that lead to changes in neuronal connectivity [34], which were probably not altered in the brains of alloxan-induced diabetic rats. For example, we recently demonstrated that brain-derived neurotrophic factor (BDNF) levels did not alter in the hippocampus from alloxan-induced diabetic rats [35]. BDNF is a neurotrophin which has an important role in hippocampal-dependent forms of memory [36].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have shown that diabetic animals presented higher depressive-like behavior in FST [28]. STZ diabetic rats showed decreased exploratory activity in OFT with a significant increase in immobility time in FST [29].…”
Section: Discussionmentioning
confidence: 83%
“…[36] Alloxan-induced diabetes in mice exhibited increased duration of immobility in FST and TST, which is consistent with the results obtained in previous studies. [7] It revealed the development of depressive episodes as a consequence of diabetes in mice. [36,37] EAV effectively reversed diabetes-induced behavioural despair effects in FST and TST without altering the generalised motor performance and the effect was similar to that of the anti-depressant drug, ESC.…”
Section: Discussionmentioning
confidence: 98%
“…[6] Earlier studies have demonstrated the consequences of depression in alloxan-induced diabetes such as decrease in duration of immobility in forced swim test (FST) and prolonged desperate behaviour and decreased exploratory activity in open field test. [7,8] Reports have shown that alloxan-induced diabetes results in increased brain monoamine oxidase (MAO) activity. [9,10] Furthermore, alloxan-induced diabetes is known to increase oxidative stress in the brain resulting in altered neuronal activity.…”
Section: Introductionmentioning
confidence: 99%